2011
DOI: 10.1007/s10461-011-9974-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Testing Uptake among Kothi-Identified Men who have Sex with Men in Public Sex Environments in Chennai, India

Abstract: Kothi-identified men who have sex with men in India are highly marginalized and are at high-risk for HIV. This study examines HIV testing among 132 self-reported HIV-negative and unknown serostatus kothis recruited from public sex environments in Chennai, India. Using logistic regression we identified variables associated with HIV testing uptake (i.e., being tested and knowing the result). Sixty-one percent reported HIV testing uptake. At the bivariate level, married men, those with low HIV transmission knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…At the personal level, lack of knowledge about HIV/AIDS was related to fear of death. Consistent with other research, (8,12) this study found that those with higher HIV knowledge are more likely to have been tested for HIV. Similarly, concerns about partner's reaction to one's HIV positive status identified in this study was consistent with a South African research (11) that found HIV testing to be delayed due to fear of potential conflict with partner.…”
Section: Barriers To Hiv Testingsupporting
confidence: 91%
“…At the personal level, lack of knowledge about HIV/AIDS was related to fear of death. Consistent with other research, (8,12) this study found that those with higher HIV knowledge are more likely to have been tested for HIV. Similarly, concerns about partner's reaction to one's HIV positive status identified in this study was consistent with a South African research (11) that found HIV testing to be delayed due to fear of potential conflict with partner.…”
Section: Barriers To Hiv Testingsupporting
confidence: 91%
“…That is, preferences for intermittent dosing, long-acting injectables, and concerns about from where and from whom to access PrEP, may be best understood in the sociocultural context of widespread stigma associated with HIV and MSM in India, and the enduring centrality, and often proximity, of family, including the prevalence of heterosexual marriage among MSM. Our previous research with MSM in India similarly identified stigma as a significant barrier to HIV testing 32 and extensive fears about HIV status disclosure. 11 Unfortunately the 2013 Indian Supreme Court decision recriminalizing samesex behaviors in India, reversing a Delhi High Court order that had decriminalized 'homosexual acts' since 2009, is likely to exacerbate these challenges to PrEP implementation, and to HIV prevention for MSM more broadly.…”
Section: Discussionmentioning
confidence: 88%
“…This explains why in most of the studies in India majority of the participants were Kothis [ 20 , 22 , 26 ]. They were also more likely to show up in investigations regarding willingness to get tested for HIV [ 27 ] or participation in vaccine trials [ 28 ] despite facing stronger barriers for accessing preventive and curative services [ 29 , 30 ]. In our study also the proportion of Panthis among participating MSM was as less as 8.62% only.…”
Section: Discussionmentioning
confidence: 99%